Advances in Visual Computing 9th International Symposium, ISVC 2013, Rethymnon, Crete, Greece, July 29-31, 2013. Proceedings, Part II - Bebis, George; Boyle, Richard; Parvin, Bahram; Koracin, Darko; Li, Baoxin; Porikli, Fatih; Zordan, Victor; Klosowski, James; Coquillart, Sabine; Luo, Xun.; Chen, Min.; Gotz, David; et al. (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
The two volume set LNCS 8033 and 8034 constitutes the refereed proceedings of the 9th International Symposium on Visual Computing, ISVC 2013, held in Rethymnon, Crete, Greece, in July 2013. The 63 revised full papers and 35 poster papers presented together with 32 special track papers were carefully reviewed and selected from more than 220 submissions. The papers are organized in topical sections: Part I (LNCS 8033) comprises computational bioimaging; computer graphics; motion, tracking, and recognition; segmentation; visualization; 3D mapping, modeling and surface reconstruction; feature extraction, matching, and recognition; sparse methods for computer vision, graphics, and medical imaging; and face processing and recognition. Part II (LNCS 8034) comprises topics such as visualization; visual computing with multimodal data streams; visual computing in digital cultural heritage; intelligent environments: algorithms and applications; applications; and virtual reality.
Visualization -- Visual computing with multimodal data streams -- Visual computing in digital cultural heritage -- Intelligent environments: algorithms and applications -- Applications -- Virtual reality.
Keywords: Computer science; Computer graphics; Computer vision; Optical pattern recognition; Bioinformatics; Computer Science; Pattern Recognition; Computer Graphics; Image Processing and Computer Vision; User Interfaces and Human Computer Interaction; Information Systems Applications (incl. Internet).; Computational Biology/Bioinformatics.